Proyecto de exportación de jaiba - Lara Avilés, Diana (2010)
The present project shows the analysis of the feasibility of the export of pulp crab frozen to the market of United States from his local production, to end of to arrive to the international markets of main consumption. For which, contemplated corresponding studies to the projection of the demand, financial analysis by means of several indicators, collection of information of both primary and secondary of the requests for his export, on the other hand we realize a technical analysis of the production to determine the ideal infrastructure Of the plant, analysis of the industry so as well a study of the objective market based in international marketing, with the purpose to determine the economic feasibility, legal and productive. Pretending generate a different and innovative option of business for the investors, in an industry that at present find in stage of growth, allow us generate new sources of employment.